Tantangan Kepemimpinan Madrasah di Era Society 5.0 - Wika, Wikalaisa; Nisa, Khairun; Sabri, Ahmad; Hidayatullah, Rully (LP2M STAI Darul Kamal NW Kembang Kerang NTB, 2024)
In carrying out the task of providing education, the role of a leader in a madrasa or school cannot be underestimated. Leadership has a crucial role in forming a vision, directing goals, and creating a learning environment that supports the development of students' potential. Madrasah or School Leadership is not just about managing administration, but also inspiring, guiding and being a role model for the entire educational community. This journal aims to examine madrasah/school leadership which includes the meaning of madrasah leadership/managers, the role of madrasah managers, the duties and responsibilities of madrasah managers. This research is library research (library research). The data analysis method used is content analysis.